Ocular manifestations of pituitary adenoma in patients presenting at a tertiary eye hospital in Nepal - Vaidya, Keepa; Tagoe, Naa Naamuah; Essuman, Yaw Akye; Poudel, Manish (Nepal Journal of Neuroscience, 2025)
Introduction: Visual outcomes following surgical resection of pituitary adenomas (PA) are generally favorable with early diagnosis and intervention. However, delayed decompression can result in irreversible visual loss, underscoring the need for prompt surgery. There is limited data from Tilganga Institute of Ophthalmology (TIO) on the demographic characteristics and visual outcomes of patients with PA. This study aims to describe the demographic profile and ocular manifestations of PA with a focus on visual symptoms, field defects, and postoperative outcomes.Materials and Methods: A retrospective longitudinal study conducted at TIO involving 24 patients (48 eyes) who underwent microscopic endonasal transsphenoidal approach of surgical resection for MRI-confirmed pituitary macroadenomas between April 2015 and March 2018. Visual presentation patterns and outcomes before and after surgery were assessed. Demographic data, clinical presentation, and visual outcomes were analyzed using IBM SPSS ver. 20 software.Results: The study included 24 patients (mean age 40.9 ± 13.3 years; range 18–79), with a male predominance (13/24, 54.2%). Most (11/24, 45.8%) presented within 1–6 months of symptom onset, with younger patients presenting earlier (p < 0.002). Blurred vision was the most common symptom (23/24, 95.8%), while bitemporal hemianopia (13/24, 54.2%) and optic atrophy (36/48,75%) were the most frequent signs. 29/48 eyes had abnormal color vision, while 16/24 patients had a relative afferent pupillary defect (RAPD). Postoperatively, visual acuity improved in 25/42 eyes (62.5%), and visual fields improved in 15 patients (62.5%).Conclusions: Timely diagnosis and surgery can significantly improve visual outcomes in pituitary adenoma patients. This study highlighted that early surgical intervention of Magnetic Resonance Imaging (MRI)-confirmed macro adenomas improved both visual acuity and visual fields in nearly 63% of eyes and patients, respectively.